Simulation of performance of air conditioning system - Mohamad Hushairy, Abdul Jalil (2012)
This thesis represents the simulation of performance of air conditioning system in the vehicle. The objective of this thesis is to analyze the relationship of performance of a car air-conditioning system and with variable speed of the compressor. The thesis describes the fundamental of air-conditioning system, the way the system works and brief explanation of each component involved in air conditioning system. The simulation was done using Matlab Software to obtain the important parameters and data. The COP indicate the performance drop due to higher speed of the compressor. The speed of compressor affects the displacement volume of the refrigerant than affected the mass flow rate of the refrigerant and remain constant. Thus the cause of the mass flow rate make the cooling capacity slightly decrease when the speed of the compressor increases but for the power input of the compressor increases due to the increasing of the compressor speed. However the simulation does not consider the mass of the refrigerant. If the mass of the refrigerant is being considered it would give a better result for the simulation of the performance of the air conditioning system.